Circularly Polarized Rectangular Micro Strip Patch Antenna Design, Analysis for C Band Applications - et. al., Dr. V. Prakasam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a days the wireless communication system development requires the low cost, low profile, minimal weight antenna development which is accomplished of continuing great presentation completed a wide frequency range. This forward-looking abilities style has supported into the MSPA (Micro Strip Patch Antenna) plan. In this administrative work presents a working recurrence of 4.85 GHz roundabout polarization rectangular miniature strip fix radio wire is planned and mimicked. The proposed rectangular miniature strip fix reception apparatus is double miniature strip-edge-took care of circularly spellbound miniature strip radio wire. The proposed receiving wire can plan and invigorate Left Hand Circular Polarization (LHCP) and Right Hand Circular Polarization (RHCP) with utilizing cross coupler is straight associated with miniature strip radio wire to get polarization of round. The proposed paper work resonant frequency or operating frequency is 4.85 GHz which is mainly used for satellite communications, full-time satellite TV networks or raw satellite feeds. This operating frequency is the IEEE 802.11a version C band frequency and this C band frequency is also used in Wi-Fi devices and Radio LAN. The proposed roundabout polarization rectangular miniature strip fix receiving wire on FR-4 (Flame Retardant and type 4) epoxy substrate material thickness of substrate is 1.6 mm. The dielectric steady of FR4 epoxy is 4.4. The double miniature strip edge took care of round polarization rectangular miniature strip fix radio wire is planned and reenacted utilizing CSTMWS (Computer Simulation Technology Micro Wave Studio) programming. The thunderous or working recurrence of proposed reception apparatus presents at 4.85 GHz for remote correspondences that gives S boundaries (return misfortune), transmission capacity and radiation example of Gain and directivity.